Dentist‐administered cognitive behavioural therapy versus four habits/midazolam: An RCT study of dental anxiety treatment in primary dental care. (7th May 2021) - Hauge, Mariann Saanum; Stora, Bent; Vassend, Olav; Hoffart, Asle; Willumsen, Tiril
Abstract: The study aimed to test the effectiveness of cognitive behavioural therapy (CBT) administered by a general dental practitioner (GDP) in a general dental practice. In a two‐arm parallel randomised controlled trial, the experimental group received a short dentist‐administered CBT‐intervention (D‐CBT). A best‐practice control group (FHM) received dental treatment during sedation with midazolam combined with an evidence‐based communication model (The Four Habits Model). Ninety‐six patients with self‐reported dental anxiety were allocated to the treatment arms at a 1:1 ratio. Modified Dental Anxiety Scale (MDAS) scores spanned from 12 to 25, and 82 patients (85%) had a score of 19 or more, indicating severe dental anxiety. In both treatment arms, scores on MDAS and Index of Dental Anxiety and Fear (IDAF‐4C) decreased significantly, but no differences were found between treatment arms. Mean reductions were: MDAS scores: −6.6 (SD = 0.5); IDAF‐4C scores: −1.0 (SD = 1.1). In conclusion, local GDPs in general dental practices with proper competence have the ability for early detection of dental anxiety and, with the use of a manual‐based D‐CBT or FHM treatment, GDPs could offer efficient first‐line treatment suitable for dental anxiety of varying severities.